(untitled) (Journal of Information Technologies in Education (ITE), 2012)
The necessity of training of the future primary-school teachers for application of information communication technologies (ICT) in their professional activity is proven in the article. The author considers the essence of the teacher’s language didactic competence, reveals constituent components of the latter, and proves the urgency of the problem of introducing the future primary school teachers to the basics of electronic language didactics as a branch of education studies.